Nickel Ion Release from Three Types of Nickel-titanium-based Orthodontic Archwires in the As-received State and After Oral Simulation - Barat Ali Ramazanzadeh; Farzaneh Ahrari; Berahman Sabzevari; Samaneh Habibi (Tabriz University of Medical Sciences, 2014)
Background and aims. This study aimed to investigate release of nickel ion from three types of nickel-titanium-based wires in the as-received state and after immersion in a simulated oral environment. Materials and methods. Forty specimens from each of the single-strand NiTi (Rematitan "Lite"), multi-strand NiTi (SPEED Supercable) and Copper NiTi (Damon Copper NiTi) were selected. Twenty specimens from each type were used in the as-received state and the others were kept in deflected state at 37ºC for 2 months followed by autoclave sterilization. The as-received and recycled wire specimens were immersed in glass bottles containing 1.8 mL of artificial saliva for 28 days and the amount of nickel ion released into the electrolyte was determined using atomic absorption spectrophotometry. Results. The single-strand NiTi released the highest quantity of nickel ion in the as-received state and the multi-strand NiTi showed the highest ion release after oral simulation. The quantity of nickel ion released from Damon Copper NiTi was the lowest in both conditions. Oral simulation followed by sterilization did not have a significant influence on nickel ion release from multi-strand NiTi and Damon Copper NiTi wires, but single-strand NiTi released statistically lower quantities of nickel ion after oral simulation. Conclusion. The multi-strand nature of Supercable did not enhance the potential of corrosion after immersion in the simulated oral environment. In vitro use of nickel-titanium-based archwires followed by sterilization did not significantly increase the amount of nickel ion released from these wires.